2021
DOI: 10.1001/jamadermatol.2021.4055
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Dermatoses and Depression

Abstract: ullous diseases affecting the skin and mucosa can have a substantial role in patients' quality of life and mental health. The most common bullous dermatoses include bullous pemphigoid and pemphigus vulgaris, which have an incidence of 4.3 and 0.1 to 0.7 per 100 000 persons worldwide, respectively. 1,2 Bullous pemphigoid and pemphigus vulgaris are both autoimmune bullous dermatoses, with antibodies to hemidesmosomes and desmoglein, respectively. 3 Epidermolysis bullosa (EB) is an inherited disorder caused by ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Apart from the potential inflammatory etiopathogenesis, AIBDs reduce an individual's self-esteem and quality of life leading to psychosocial effects inclusive of depression [16]. Previous studies have indicated that the prevalence of depressive symptoms ranges from 40% to 80%, while that of major depression ranges from 11.4% to 28% [12]. This is significantly lower than the prevalence observed in our clinic.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Apart from the potential inflammatory etiopathogenesis, AIBDs reduce an individual's self-esteem and quality of life leading to psychosocial effects inclusive of depression [16]. Previous studies have indicated that the prevalence of depressive symptoms ranges from 40% to 80%, while that of major depression ranges from 11.4% to 28% [12]. This is significantly lower than the prevalence observed in our clinic.…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, there is no local study characterizing the mental health of patients with autoimmune bullous diseases (AIBDs). Given the lack of local data on this subject [12], we conducted a cross-sectional study to determine the prevalence and severity of clinically undiagnosed depression in patients with AIBDs.…”
Section: Introductionmentioning
confidence: 99%
“…10.7% vs 4.3%, respectively, p = 0.0005). Of the 13 cases of a Alopecia areata, vitiligo, urticaria.…”
mentioning
confidence: 87%
“…BP has been linked with a variety of comorbidities, including neurological illnesses (multiple sclerosis, dementia, Parkinson’s disease, epilepsy, and stroke) ( 8 ); an elevated risk of thromboembolic events ( 9 ); psychiatric disorders ( 10 ); dermatoses (psoriasis and lichen planus) ( 11 , 12 ); and various medications ( 13 ). The link between BP and malignancy has also been studied with conflicting results.…”
mentioning
confidence: 99%
“… 50 A recent systematic review has shown that the prevalence of depressive symptoms and clinical depression among patients with autoimmune bullous disorders (AIBDs) ranged from 40 to 80% and 11.4 to 28%, respectively. 51 Wohl et al 52 evaluated records of 764 individuals in Israel (255 pemphigus patients and 509 controls) and found that depression was higher in pemphigus patients with an odds ratio of 1.19 (95% confidence interval (CI): 1.12-1.27). Similarly, Hsu et al 53 analyzed 4600 medical records in Taiwan (926 pemphigus patients and 3674 controls) and reported that pemphigus patients were more likely to suffer from depression with an adjusted hazard ratio of 1.99 (95% CI: 1.37-2.86).…”
Section: Psychosocial Burdenmentioning
confidence: 99%